Ministers of the Kingdom of Morocco between appointment and exemption: since the Government of 7 December 1955 to the Government of January 3, 2012 - El Baz, Khawla (Journal of Economic, Administrative and Legal Sciences, 2018)
This study attempts to reveal the procedure used in appointing the members of the Moroccan government in the first demand, as well as the procedure for exempting them from their duties in the second demand. Because, the procedure for the appointment of ministers seems evident. but, it isn't.Because of this, the research highlighted that, this procedure is divided into two categories: total appointment and partial appointment, which are divided into two other types.After that, this study tried to give a statement about the inauguration of the government, because of, the five Moroccan constitutions didn't stipulated about the inauguration of the government before, which created a problem, Is it from the date of the designation of the members of the government by the King? Or is it the date declared by the royal decrees? Or is it after having obtained the confidence of the Chamber of Representatives?Also, this research spotlight about dismissal and resignation created to ministers a major issue for discussion, concerning, if they could resign individually?
Keywords: Moroccan ministers; Moroccan government; appointment procedure; dismissal procedure